Análise da implantação de reservatórios de detenção na bacia São Pedro e modelagem hidrodinâmica da avenida Rondon Pacheco - Vergütz, Laila Atyna Alves (2016)
Due to increasing of urban occupation, and subsequent soil sealing, there is an increase in the runoff coefficient, causing more frequent floods than those that existed when the surface was permeable. The city of Uberlândia / MG has suffered from episodes of significant flooding. The place where these floods occur, is the Governador Rondon Pacheco Avenue, whose basin has high urbanization. This study aims to evaluate the basin of the stream São Pedro in Uberlândia / MG, and suggest detention basins, determined with the aid of HEC-HMS, in order to minimize the effects in this region. The unidirectional hydrodynamic modeling, through the HEC-RAS software, resulted in the heights of the water surface profiles in the avenue considering the pre-urbanization scenario, the current scenario and with the inclusion of the reservoirs proposed in this research. The results show that before the urban occupation the height of the water surface profile, at the most critical point of the avenue, reaches 85 cm above the ground. After urbanization without the reservoirs, this value is 142 cm, with an increase of 67% compared to the level of water into the pre-urban scenario. In the case studied here, with the insertion of the proposed reservoirs in the sub-basins of the São Pedro Alto and Lagoinha the height of the water surface profile is 112 cm. Therefore this measure does not solve the problems caused by rain with recurrence period of 100 years, since prior to urbanization, the level of water already reaches values higher than the capacity of the existing sewer, affecting the population that is currently allocated in Governador Rondon Pacheco Avenue's region.